2020
DOI: 10.1101/2020.02.11.943613
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Site wind right: Identifying low-impact wind development areas in the Central United States

Abstract: To help avoid the most catastrophic effects of climate change, society needs to achieve net-zero greenhouse gas emissions by mid-century. Wind energy provides a clean, renewable source of electricity; however, improperly sited wind facilities pose known threats to wildlife populations and contribute to degradation of natural habitats. To support a rapid transition to low-carbon energy while protecting imperiled species, we identified potential low-impact areas for wind development in a 17-state region of the c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Three other scenarios also reach zero net emissions in 2050, while meeting additional constraints. The (iv) low land case tests the effect of limitations on land use in response to concerns about the sustainability of biomass use (Fletcher et al, 2011;IPCC, 2019;Searchinger et al, 2008;Smith et al, 2013) and the land requirements for siting renewable energy and transmission facilities (Hise et al, 2020;Kahn, 2000;McDonald et al, 2009;Wu et al, 2016Wu et al, , 2020. In this scenario, the land area of onshore wind and utility-scale solar was limited to 50% of the central case value, and the biomass supply was limited to 50% of its technical potential (Langholtz et al, 2016).…”
Section: Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…Three other scenarios also reach zero net emissions in 2050, while meeting additional constraints. The (iv) low land case tests the effect of limitations on land use in response to concerns about the sustainability of biomass use (Fletcher et al, 2011;IPCC, 2019;Searchinger et al, 2008;Smith et al, 2013) and the land requirements for siting renewable energy and transmission facilities (Hise et al, 2020;Kahn, 2000;McDonald et al, 2009;Wu et al, 2016Wu et al, , 2020. In this scenario, the land area of onshore wind and utility-scale solar was limited to 50% of the central case value, and the biomass supply was limited to 50% of its technical potential (Langholtz et al, 2016).…”
Section: Scenariosmentioning
confidence: 99%
“…As described earlier, the land requirements for wind and solar electricity based on rules of thumb in the literature ranged from 17 to 48 MHa (Table 2). For comparison, a recent study by The Nature Conservancy found an area of 36 MHa to be suitable for wind development with low environmental impacts in the 17-state wind belt in the central United States (Hise et al, 2020).…”
Section: Fuel Supplymentioning
confidence: 99%
“…Agriculture, tourism, and fishing industries may be impacted if land is cleared or coastal areas become inaccessible due to solar or wind developments (Nesamalar et al 2017;Seetharaman et al 2019). Wind developments (both on-and offshore) have also sparked opposition from military stakeholders, who cite potential interference with surveillance activities, air traffic and radar systems, and low-level flights (Durkay and Schultz 2016).…”
Section: Potential Land-use Conflicts Can Occur Between New Clean Energy Developments Existing Local Industries and Conservation Needs Anmentioning
confidence: 99%